(untitled) (Economic and Political Thought, 2012)
As a result of the dynamic growth of the LNG market, natural gas is becoming the pillar that helps to build global energy security. Additionally, there are also other important elements such as the global attempts to protect the natural environment, the consequences of the nuclear catastrophe in Japan, still low price competitiveness of renewable energy sources, the economic crisis forcing most economies in the world cut costs, and – finally – the development of new technologies that make it possible to extract gas from unconventional sources. The latest factor, originating in the United States, created opportunities for that country to join the group of global LNG exporters.